Myocardial iron overload in thalassaemia major. How early to check?. (February 2014) - Borgna‐Pignatti, Caterina; Meloni, Antonella; Guerrini, Giulia; Gulino, Letizia; Filosa, Aldo; Ruffo, Giovan B.; Casini, Tommaso; Chiodi, Elisabetta; Lombardi, Massimo; Pepe, Alessia
Summary The age at which it is necessary to start Cardiovascular Magnetic Resonance (CMR) T2* screening in thalassaemia major (TM) is still uncertain. To clarify this point, we evaluated the prevalence of myocardial iron overload (MIO), function and fibrosis by CMR in TM patients younger than 10 years. We retrospectively selected 35 TM patients enrolled in the Myocardial Iron Overload in Thalassaemia network. MIO was measured by T2* multislice multiecho technique. Biventricular function parameters were evaluated by cine images. To detect myocardial fibrosis, late gadolinium enhancement images were acquired. Patients' age ranged from 4·2 to 9·7 years. All scans were performed without sedation. Nine patients showed no MIO, 22 patients had heterogeneous MIO with a T2* global value ≥20 ms; two patients had heterogeneous MIO with a T2* global value <20 ms and two patients showed homogeneous MIO. No patient showed myocardial fibrosis. Among the patients with heart T2*<20 ms, the youngest was 6 years old, none showed heart dysfunction and the iron transfused was <35 g in all cases. Cardiac iron loading can occur much earlier than previously described. The first cardiac T2* assessment should be performed as early as feasible without sedation, especially if chelation is started late or if poor compliance is suspected.